LETTING THE LEARNERS LEAD: ADAPTING FCM TO ENHANCE LEARNER MOTIVATION, INTERACTION AND ACADEMIC ACHIEVEMENT - Preece, Abdul Shakour; Hamed, Popoola Kareem (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2018)
The purpose of the research was to establish whether ‘blended learner-led learning’ could impact learners’ motivation, interaction and academic achievement. The researchers set about adapting Flipped Classroom Method by allowing small teams of undergraduate students to share the responsibility of preparing online materials and then administering them using Flipped Classroom Method, under the guidance and supervision of the lecturer. Flipped Classroom Method is currently a popular pedagogical approach that utilizes instructional technology combining face to face learning with online learning. This has a number of advantages: it allows learners to access materials online at any time or place and engages learners in a more active, constructivist learning environment. However, it poses challenges for teachers and students who are more used to a conventional approach to teaching and learning because it challenges a traditional teacher-student relationship where the teacher is seen as the central authority for knowledge and learning. Moreover, it requires a lot of effort on the part of the teacher to prepare all the online resources. The researchers conducted a quasi-experiment with an undergraduate course called 'Curriculum and Instruction' that lasted five weeks. The purpose was to see the effects of blended learner-led learning on students’ motivation, interaction and academic achievement. The results show that blended learner-led learning had a statistically significant impact on all three for the experimental group. Consequently, it represents a viable alternative for instructors seeking a constructivist pedagogy that maintains adab and respect for the teacher.